2020
DOI: 10.2196/15748
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Hands-On Informatics Skills to Future Health Informaticians: A Competency Framework Proposal and Analysis of Health Care Informatics Curricula

Abstract: Background Existing health informatics curriculum requirements mostly use a competency-based approach rather than a skill-based one. Objective The main objective of this study was to assess the current skills training requirements in graduate health informatics curricula to evaluate graduate students’ confidence in specific health informatics skills. Methods A quantitative cross-sectional observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Even though several organizations, agencies, and work groups such as the International Medical Informatics Association [ 47 ], the Commission on Accreditation for Health Informatics and Information Management Education [ 48 , 49 ], the Health Informatics Society of Australia [ 50 ], the TIGER (Technology Informatics Guiding Education Reform) Initiative [ 51 ], and the Association of American Medical Colleges [ 52 ] published skill recommendations for health informatics curricula, they have not determined specific skill sets for AI education. Furthermore, a recent study evaluated health informatics students' skills in developing AI apps and emphasized the need to develop new competencies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though several organizations, agencies, and work groups such as the International Medical Informatics Association [ 47 ], the Commission on Accreditation for Health Informatics and Information Management Education [ 48 , 49 ], the Health Informatics Society of Australia [ 50 ], the TIGER (Technology Informatics Guiding Education Reform) Initiative [ 51 ], and the Association of American Medical Colleges [ 52 ] published skill recommendations for health informatics curricula, they have not determined specific skill sets for AI education. Furthermore, a recent study evaluated health informatics students' skills in developing AI apps and emphasized the need to develop new competencies [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory accreditation and individual certification of forensic science professionals should be mandatory, and all forensic science professionals should have access to a certification process. In determining appropriate standards for accreditation and certification, the AFLAC will consider recognized and established international standards such as those developed by the ISO [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of our study showed that most common hiring organizations were health system and hospitals followed by academic institutes. Recent studies highlight the need for informatics training in the public health workforce [35]. Similarly, the Council on Education for Public Health (CEPH) includes informatics as a foundational competency for accreditation of public health programs.…”
Section: Discussionmentioning
confidence: 99%